The determination of the radiation dose and image quality for abdominal radiography using a digital X-ray machine without an automatic exposure control system at King Chulalongkorn Memorial Hospital - Suwanpradit, Petcharleeya; Wongvit-olan, Suppakit; Kongthana, Onjira; Komprasert, Warinthorn; Luechabhun, Chawee; Ariyachaipanich, Aticha; Arjhansiri, Kiat; Apipunyasopon, Lukkana (The Thai Journal of Radiological Technology, 2023)
Background: Radiographic procedures with automatic exposure control (AEC) system are the exposure technique to obtain the optimal diagnostic image quality. However, there is a higher dose under AEC compared with a lack of AEC. Objective: The aim of this study was to determine the radiation dose and image quality for abdominal digital radiography of human-like phantom using a routine clinical protocol with AEC and a modified protocol without AEC at King Chulalongkorn Memorial Hospital. Methods: A digital X-ray system (Digital Diagnost, Philips) with a CsI:Ti image receptor and the human-like phantom (PBU-60, Kyoto Kagaku) were used. The abdominal anteroposterior (AP) projections were performed with and without AEC systems. The entrance surface air kerma (ESAK) was measured on the phantom surface using optically stimulated luminescence dosimeters (OSLDs), while the kerma area product (KAP) was simultaneously recorded. The qualitative image quality was scored by two experienced radiologists. Results: We found that the ESAK and KAP values trended to the similar direction. The ESAK obtained from the modified parameter without AEC (81 kVp and 3.2 mAs) was lower by 90% compared to the routine clinical parameter with AEC (85 kVp and 32 mAs), while the optimal image quality was maintained in the acceptable level for diagnostic abdominal radiography. Conclusion: Applying the exposure parameter without AEC for abdominal digital radiography reduces the radiation while the image quality is optimal for diagnosis.